Supply Chain Management in Flyover Projects in India - Yadav, Sudhir; Ray, Gargi Sojitra (Penerbit Universiti Sains Malaysia, 2015)
This paper explores the application of supply chain management (SCM) in the Indian construction industry. The authors studied the SCM practices followed in flyover projects and compared them with the seamless SCM model for construction proposed by a previous study. A case study approach was followed for the research work. Structured interviews were conducted to understand the SCM practices in flyover projects in India. The developed model advocates leading roles for client and strategic needs analysis and value management study that are missing in the studied projects. All of the projects studied faced cost and time overruns. The seamless SCM model may be extended to developing countries by incorporating requirements related to the long-term relationship between project agents and, if possible, by suggesting that clients should not select agents using only the minimal cost criteria. The extended model also proposes SCM training for all project agents before the start of the project. Strategic needs analysis and value management study should be an integral part of the construction project to improve project efficiency. Implementing the seamless SCM model calls for the early involvement (i.e., at the project design stage) of all project agents. Project sponsors can apply the findings of this study to manage time and cost overruns.